Interactions of Pertechnetate with Proteins: An in-Silico Study - Trusova, V.; Kuznietsov, P.; Yakymenko, I.; Gorbenko, G. (East European Journal of Physics, 2026)
Technetium 99m is a radionuclide extensively used in clinical practice due to a range of its properties among which are short half-life, reduced radiation exposure and toxicity, short labeling time, high target to non-target ratio and low cost. In its highest oxidation state +VII, technetium exists in the form of pertechnetate ([TcO4]−) that serves as an effective imaging agent. One important determinant of pharmacokinetics and bioavailability of pertechnetate involves the possibility of its complexation with blood proteins. In the present work we performed in silico study of the pertechnentate complexes with three blood proteins, deoxyhemoglobin, albumin and transferrin. The molecular docking of [TcO4]−  to the examined proteins provided evidence for pertechnetate localization in the protein structural cavities containing positively charged amino acid residues, with the highest binding affinity being obverved for deoxyhemoglobin. At the same time, the molecular dynamics simulations indicated that, in contrast to deoxyhemoglobin, only the complexes of pertechnetate with plasma proteins albumin and transferrin remain stable and do not show significant variations in root mean square deviation of atomic positions, solvent accessible surface area, radius of gyration and secondary structure per residue. The results obtained may help in better understaning of pertechnetate pharmacokinetic behavior and enhancing its efficiency as an imaging agent.